Corporate Social Responsibility, Konservatisme Akuntansi, Timeliness dan Earning Rensponse Coefficient dengan Leverage sebagai Variabel Moderasi - Holiawati Holiawati; Astri Melani Rizky; Endang Ruhiyat (Universitas Pamulang, 2022)
The aim of this research is to determine the effect of corporate social responsibility, accounting conservatism and timeliness and then leverage it as a moderate variable toward earning response coefficient in consumer goods sub-sector manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during 2016-2019. This research is a quantitative study with 28 total samples which is there are 112 data researched. Based on the T-test it result is known that the accounting conservatism variable and leverage-moderated corporate social responsibility variable affect toward earning response coefficient. The timeliness variable and leverage-moderated timeliness have a negative influence on the earning response coefficient. Meanwhile, the corporate social responsibility variable and the leverage-moderated accounting conservatism are not affected by the earning response coefficient